Low-Symmetry Mesoporous Titanium Dioxide (lsm-TiO2) Electrocatalyst for Efficient and Durable Oxygen Evolution in Aqueous Alkali. Issue 7 (1st January 2018) - Amer, Mabrook S.; Ghanem, Mohamed A.; Al-Mayouf, Abdullah M.; Arunachalam, Prabhakarn
Abstract : The electrochemical splitting of water requires highly active, robust, and economical electrocatalysts. Titanium dioxide, a semiconductor, is an inactive oxygen evolution electrocatalyst because of its low conductivity and poor reactivity. Here, thin film of a low-symmetry (short-range order) mesoporous titanium dioxide ( lsm -TiO2 ) electrocatalysts having about 200 m 2 g −1 surface area and semi-crystalline anatase wall were prepared by evaporation-induced self-assembly (EISA) approach, followed by a two-step calcination process. The porosity, order, surface area, crystallinity and activity of lsm -TiO2 are controlled by tuning the titanium precursor/surfactant ratio. The lsm -TiO2 catalyst with a precursor/surfactant ratio of 1.5 wt% showed unprecedented electrocatalytic activity and substantial shift in the oxygen evolution onset potential to 1.55 V vs. RHE (overpotential ca. 320 mV), small Tafel slope (51 mv dec −1 ) and charge transfer resistance, and current density of 11 mA cm −2 was obtained at 1.65 V vs. RHE, significantly more efficient than highly ordered hexagonal mesoporous TiO2 counterpart and comparable to state-of-the-art transition metal oxide electrocatalysts. Furthermore, the lsm-TiO2 electrode has excellent durability and is activated during electrolysis with no visible current decays or potential drifting is observed after 12.0 h of electrolysis, demonstrating the promise of this low-symmetry mesoporous TiO2 as an electrocatalyst for energy conversion technologies.